Overcoming tensions between family-centered care and fidelity within Early Intervention implementation research. (April 2023) - Pickard, Katherine; Wainer, Allison; Broder-Fingert, Sarabeth; Sheldrick, R. Christopher; Stahmer, Aubyn C.
The Part C Early Intervention system has been a focus of translational efforts in the autism field, as it is an entry point to services during a critical window of early development. Although Early Intervention systems are perceived as a promising setting in which to implement evidence-based practices for autism, implementation efforts seldom account for the unique service delivery model of Early Intervention systems, which emphasize family-centered care. The principles of family-centered care may at times pose tradeoffs to the implementation of manualized evidence-based practices and, thus, are pertinent to consider within implementation research being conducted within these systems. This commentary highlights family-centered care as an important factor of service delivery in Early Intervention systems that deserve greater attention. We lay out how family-centered care provides a framework for evaluating evidence-based practice adaptation in Early Intervention systems, how it may impact the adoption and implementation of evidence-based practices, and directions for future research to evaluate the impact of family-centered care alongside evidence-based practice delivery. Measuring family-centered care as part of research within Early Intervention systems may shift the autism field to a more balanced view of fidelity as both delivering core evidence-based practice components in a manner that closely align with fundamental tenants of Early Intervention systems. Lay Abstract: Early Intervention systems provide therapeutic services to families of young children birth to 3 years with developmental delays and are considered a natural access point to services for young children and their families. Research studies in the autism field have been interested in training providers to deliver evidence-based practices in Early Intervention systems to increase access to services for young children with an increased likelihood of being autistic. However, research has often overlooked that Early Intervention systems prioritize family-centered care, an approach to working with families that honors and respects their values and choices and that provides supports to strengthen family functioning. This commentary points out that family-centered care deserves greater attention in research being done in Early Intervention systems. We describe how family-centered care may shape how interventions are delivered, and discuss directions for future research to evaluate the impact of family-centered care alongside intervention delivery.